This totally bites! - Ames Ruth 1924-2022; Ruth Ames (New York : Scholastic, 2010)
"Twelve-year-old Emma-Rose Paley has always felt very different from her bubbly, outgoing parents. Unlike them, Emma-Rose has pale skin and jet-black hair, she prefers gray weather to sunshine, and she hates the taste of garlic. When Emma-Rose's great-aunt Margo comes to visit from Romania, Emma-rose uncovers a dark family secret and has a sudden revelation. Could Emma-Rose be a real, live vampire?" (publisher).
M
740
Keywords: Fiction; Vampires